Polaritons in a nonideal array of ultracold quantum dots - Rumyantsev, V.V.; Fedorov, S.A.; Gumennyk, K.V. (Физика низких температур, 2016)
We develop a numerical model for a defect-containing square lattice of microcavities with embedded ultracold atomic clusters (quantum dots). It is assumed that certain fractions of quantum dots and cavities are absent, which leads to transformation of polariton spectrum of the overall structure. The dispersion relations for polaritonic modes are derived as functions of defect concentrations and on this basis the band gap, the effective masses of lower and upper dispersion branch polaritons as well as their densities of states are evaluated.